Effects of corticotropin-releasing hormone on the expression of adenosine triphosphate-sensitive potassium channels (Kir6.1/SUR2B) in human term pregnant myometrium - Joo Young Kim; Wen Hao Wu; Jin Hyun Jun; Jeenah Sohn; Yong Soo Seo (Obstetrics & Gynecology Science, 2018)
ObjectiveCorticotropin-releasing hormone (CRH) is a crucial regulator of human pregnancy and parturition. Adenosine triphosphate (ATP)-sensitive potassium (KATP) channels are important for regulating myometrial quiescence during pregnancy. We investigated regulatory effects of different concentrations of CRH on KATP channel expression in human myometrial smooth muscle cells (HSMCs) in in vitro conditions.MethodsAfter treating HSMCs with different concentrations of CRH (1, 10, 102, 103, 104 pmol/L), mRNA and protein expression of KATP channel subunits (Kir6.1 and SUR2B) was analyzed by reverse transcription-polymerase chain reaction and western blot. We investigated which CRH receptor was involved in the reaction and measured the effects of CRH on intracellular Ca2+ concentration when oxytocin was administered in HSMCs using Fluo-8 AM ester.ResultsWhen HSMCs were treated with low (1 pmol/L) and high (103, 104 pmol/L) CRH concentrations, KATP channel expression significantly increased and decreased, respectively. SUR2B mRNA expression at low and high CRH concentrations was significantly antagonized by antalarmin (CRH receptor-1 antagonist) and astressin 2b (CRH receptor-2 antagonist), respectively; however, Kir6.1 mRNA expression was not affected. After oxytocin treatment, the intracellular Ca2+ concentration in CRH-treated HSMCs was significantly lowered in low concentration of CRH (1 pmol/L), but not in high concentration of CRH (103 pmol/L), compared to control.ConclusionOur data demonstrated the regulatory effect was different when HSMCs were treated with low (early pregnancy-like) and high (labor-like) CRH concentrations and the KATP channel expression showed significant increase and decrease. This could cause inhibition and activation, respectively, of uterine muscle contraction, demonstrating opposite dual actions of CRH.